India-As The Emerging Economic Super Power And Recession Champion (Trinity Journal of Management, IT & Media (TJMITM), 2012)
We all know money rules the world. Hence the economic  health is the biggest parameter of the growth of any nation.  Similarly economic recessions are dark realities faced by  world’s most of the economies whether big or small, grown  or growing and even the third world. But the whole world is  watching the growth of new economies like China, Russia,  India, Brazil, and Mexico. These economies have faced,  struggled and survived the recession better than expected  by the world. This success is called ‘The Rise of the Rest’ the modern economic phenomenon, and is described by  Freed Zakaria in his book ‘The Post - American World’. The  rest here means the countries other than America. There  are too many questions floating in air, the major one’s are:  What is quantum or size of economic recession? How has  it affected the various countries around the world? Which  countries survived the economic recession the best? What  is the status of Indian economy in these turbulent times?  This secondary data based research article is an attempt  to answer the above major questions and present a clear  picture as to why and how India managed to survive the  recession of 2008, and later.
Keywords: Recession; Developing economy; economic superpower; globalization; survival strategy